Pengaruh Pengetahuan, Religiusitas Dan Akses Media Informasi Terhadap Minat Berwakaf Sukuk Wakaf - Adenia Rachma; Mardiana Mardiana (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims to determine how the influence of knowledge, religiosity, and access to information media on interest in waqf sukuk. This research is a quantitative type of research using Smartpls as a data analysis tool, while the population in this study are state university students in the city of Malang with a sample of 120 students. The results of this study explain that knowledge has a positive and significant influence on interest in waqf sukuk. Then religiosity has a positive but not significant effect on interest in waqf sukuk. And access to information media has a positive and significant influence on interest in waqf sukuk.